Tight Glycemic Control With Insulin Does Not Affect Skeletal Muscle Degradation During the Early Postoperative Period Following Pediatric Cardiac Surgery*. Issue 6 (July 2015) - Fisher, Jeremy G.; Sparks, Eric A.; Khan, Faraz A.; Alexander, Jamin L.; Asaro, Lisa A.; Wypij, David; Gaies, Michael; Modi, Biren P.; Duggan, Christopher; Agus, Michael S. D.; Yu, Yong-Ming; Jaksic, Tom
Abstract : Objective: Critical illness is associated with significant catabolism, and persistent protein loss correlates with increased morbidity and mortality. Insulin is a potent anticatabolic hormone; high-dose insulin decreases skeletal muscle protein breakdown in critically ill pediatric surgical patients. However, insulin's effect on protein catabolism when given at clinically utilized doses has not been studied. The objective was to evaluate the effect of postoperative tight glycemic control and clinically dosed insulin on skeletal muscle degradation in children after cardiac surgery with cardiopulmonary bypass. Design: Secondary analysis of a two-center, prospective randomized trial comparing tight glycemic control with standard care. Randomization was stratified by study center. Patients: Children 0–36 months who were admitted to the ICU after cardiac surgery requiring cardiopulmonary bypass. Interventions: In the tight glycemic control arm, insulin was titrated to maintain blood glucose between 80 and 110 mg/dL. Patients in the control arm received standard care. Skeletal muscle breakdown was quantified by a ratio of urinary 3-methylhistidine to urinary creatinine. Measurements and Main Results: A total of 561 patients were included: 281 in the tight glycemic control arm and 280 receiving standard care. There was no difference in 3-methylhistidine to creatinine between groups (tight glycemic control, 249 ± 127 vs standard care, 253 ± 112, mean ± SD in μmol/g; p = 0.72). In analyses restricted to the patients in tight glycemic control arm, higher 3-methylhistidine to creatinine correlated with younger age, as well as lower weight, weight-for-age z score, length, and body surface area ( p < 0.005 for each) and lower postoperative day 3 serum creatinine ( r = –0.17; p = 0.02). Sex, prealbumin, and albumin were not associated with 3-methylhistidine to creatinine. During urine collection, 245 patients (87%) received insulin. However, any insulin exposure did not impact 3-methylhistidine to creatinine ( t test, p = 0.45), and there was no dose-dependent effect of insulin on 3-methylhistidine to creatinine ( r = –0.03; p = 0.60). Conclusion: Although high-dose insulin has an anabolic effect in experimental conditions, at doses necessary to achieve normoglycemia, insulin appears to have no discernible impact on skeletal muscle degradation in critically ill pediatric cardiac surgical patients.